ORGANOCHLORINE PESTICIDE-RESIDUES IN HUMAN-MILK IN THE RIBEIRAO-PRETO REGION, STATE OF SAO-PAULO, BRAZIL - Matuo, Y. K.; Lopes, JNC; Casanova, I. C.; Matuo, T.; Lopes, JLC (Springer, 1992)
Thirty-seven samples of human milk (colostrum) from donors living in the Ribeirao Preto region were analyzed to determine the levels of organochlorine pesticide residues. Donors were classified into two groups, i.e., occupationally exposed and non-exposed to pesticides. Other factors such as age, previous lactations, race, smoking habit, occupation, family income and educational level were also considered. Analysis was performed by preliminary lipid extraction followed by fractional partition on a column and finally by gas chromatography with an electron capture detector. Lindane was found in 32% of the samples in amounts of less than 0.001 mg/kg; heptachlor was found in 65% of the samples at mean levels of 0.001 mg/kg, i.e., a level five-fold lower than that established by FAO/WHO (1970) for cow's milk. Aldrin and endrin were not detected in any of the samples. Dieldrin was detected in only one sample at a level of 0.038 mg/kg, which is considered high. DDT and DDE amounts are reported as total DDT and at least one of these compounds was present in every sample. Amounts detected in donors occupationally exposed to pesticides ranged from 0.008 to 0.455 mg/kg (mean, 0.149 mg/kg), i.e., three times the limit established by FAO/WHO (1970), while values for donors who had not been exposed ranged from 0.002 to 0.072 mg/kg (mean, 0.025 mg/kg), i.e., half the limit. Considering the level of acceptable daily intake proposed by FAO/WHO (1973), lactents ingested 1% of the acceptable intake of lindane (all donors), 30% of the acceptable intake of heptachlor (all donors), 60% of the acceptable intake of DDT (non-exposed donors), and 3.7 times the acceptable intake of DDT (exposed donors). Comparing the present results with those obtained 10 years ago, the total DDT level in human milk is decreasing in this part of the country. The mean amount of organochlorine residues in non-exposed women's milk was one of the lowest levels among those recorded in the literature. DDT levels of occupationally exposed women's milk were comparable with those reported for developed countries and lower than those detected in Latin American countries. When the results of this survey are considered in relation to the advantages of breast-feeding, the risk-benefit balance is still favorable to breast-feeding. However, given the lack of long-term epidemiological studies, undesirable or harmful long-lasting effects cannot be excluded.